Determinan Tingkat Kepuasan Penulis Terhadap Tata Kelola Jurnal Ilmiah - Putri, Zuwesty Eka (Faculty of Economic and Business, 2018)
Customer satisfaction is one of the important things in improving service quality. This study aims to examine the factors that influence the level of author satisfaction in the management of scientific journals. Also, this study also aims to map the strengths and weaknesses of journal management at State Islamic University (UIN) Syarif Hidayatullah Jakarta. The analysis technique used in this study is multiple regression and SWOT analysis. The results showed that the determinants of satisfaction level were physical appearance, reliability, and quality of articles. Also, this study shows SWOT results in quadrant V. Institutions found in quadrant V can implement hold and maintain strategies.DOI:10.15408/ess.v8i2.7957